LEXICAL AND FOLK KNOWLEDGE COMPETENCE AS A COMPONENT OF FUTURE PRIMARY SCHOOL TEACHERS’ PROFESSIONAL SPEECH - Lutsan, Nadia; Struk, Anna; Barylo, Svitlana; Bai, Ihor; Varvaruk, Mariana (Revista Inclusiones, 2020)
The article highlights the features of lexical and folk knowledge competence as a component of future primary school teachers’ professional speech. The aim of the study is to determine the state of primary school teachers’ lexical and folk knowledge competence formation. It was developed a diagnostic methodology and criteria for the formation of lexical and folk knowledge competence of the future primary school teacher. The criteria of the pointed competence are: cognitive, reproductive and reflexive evaluation. Each criterion includes a group of qualitative indicators that reveal the content and characterize the students’ achievements in a particular type of activity. On this foundation, the methodological tools were developed, run psychological and pedagogical diagnostics of the formation of this professional quality of future primary school teachers. This allowed us to classify them quantitatively by high, sufficient, average and low levels of formation with specific characteristics of qualitative measurements, which opens up the prospects for developing appropriate effective measures in order to improve the quality of future teachers’ professional training.